Strategic Surgical Management of Complex Ovarian Masses During Second-Trimester Pregnancy: A Serial Case Report - Christian Homenta; Febia Erfiandi; Kemala Isnainiasih Mantilidewi (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Introduction: Ovarian masses are found in about 1.5% – 5.7% of pregnancies, with suspicion of malignancy in 1% – 6% of cases. Large or complex adnexal masses can increase the risk of torsion, rupture, or malignant transformation. This report aims to highlight the importance of personalized surgical management of ovarian masses during pregnancy, particularly emphasizing the benefits of second-trimester intervention, and to explore the research question: Can elective adnexal surgery during the second trimester improve maternal and fetal outcomes in high-risk pregnancies? Case Report: Two pregnant patients with adnexal masses were evaluated clinically and radiologically. Decision-making was based on gestational age, mass characteristics, and maternal-fetal considerations. Both underwent surgical management in the second trimester, with histopathological confirmation obtained. Case 1: A 37-year-old G5P3A1 at 16 weeks’ gestation presented with a multilocular cystic mass (25×12×8 cm) in the right ovary. Salpingo-oophorectomy at 19 weeks revealed a benign non-papillary cyst. Case 2: A 24-year-old G3P2A0 at 23 weeks’ gestation had a complex adnexal mass (20×20×15 cm). Partial oophorectomy revealed sebaceous material, hair, and cartilage. Histopathology confirmed a mature cystic teratoma. The pregnancy progressed uneventfully, culminating in spontaneous vaginal delivery at term.Conclusion: This case report emphasizes the importance of prompt surgical intervention during the second trimester of pregnancy. It offers unique insights into the strategic management of complex ovarian masses, contributing valuable information to the limited literature and guiding clinical decision-making in similar cases. Abstrak Pendahuluan: Massa ovarium ditemukan pada sekira 1,5% – 5,7% kehamilan, dengan kecurigaan keganasan pada 1% – 6% kasus. Massa adneksa yang besar atau kompleks dapat menimbulkan risiko torsi, ruptur, atau transformasi ganas. Laporan ini bertujuan untuk menyoroti peran penatalaksanaan bedah individual pada massa ovarium selama kehamilan, khususnya dengan menekankan keuntungan intervensi pada trimester kedua, serta menjawab pertanyaan penelitian: Dapatkah pembedahan adneksa elektif pada trimester kedua mengoptimalkan luaran maternal dan janin pada kehamilan berisiko tinggi?Laporan Kasus: Dua pasien hamil dengan massa adneksa dievaluasi secara klinis dan radiologis. Pengambilan keputusan didasarkan pada usia kehamilan, karakteristik massa, dan pertimbangan maternal-janin. Keduanya menjalani penatalaksanaan bedah pada trimester kedua, dan konfirmasi histopatologi diperoleh. Kasus 1: Wanita 37 tahun G5P3A1 pada usia kehamilan 16 minggu dengan massa kistik multilokular (25×12×8 cm) pada ovarium kanan. Salpingo-ooforektomi pada usia kehamilan 19 minggu menunjukkan kista jinak non-papiler. Kasus 2: Wanita 24 tahun G3P2A0 pada usia kehamilan 23 minggu dengan massa adneksa kompleks (20×20×15 cm). Ooforektomi parsial menunjukkan adanya material sebaceous, rambut, dan kartilago. Histopatologi mengonfirmasi teratoma kistik matur. Kehamilan berlangsung tanpa komplikasi dan berakhir dengan persalinan spontan pervaginam aterm.Kesimpulan: Pembedahan adneksa elektif pada trimester kedua memberikan kondisi anatomi dan obstetri yang optimal, serta meminimalkan risiko teratogenik dan persalinan prematur. Dengan pendekatan individual, multidisipliner, dan berbasis bukti, strategi ini dapat memberikan luaran maternal dan neonatal yang baik pada kehamilan berisiko tinggi terpilih.